The adoption of capability maturity model (CMM) in software development and integration organisation in Klang Valley / Ili Bazilah Razmi - Razmi, Ili Bazilah (2005)
What is CMM and why is it important? CMM is the Capability Maturity Model developed by the Software Engineering Institute (SEI) at Carnegie Mellon University. It is a model that provides a way to assess the maturity (i.e. strength) of the processes used by an organization to develop and support its information systems. Since these processes are the tools by which the organization accomplishes its work, the higher their quality, the higher the performance of the organization. An organization that employs processes that comply with a higher CMM level produces higher quality work products faster, for less cost, and with greater consistency. However, the adoption of new practices takes time and planning. When implementing new practices, it is important not to underestimate the effort for the new behaviors to become common practice within the organization. The research paper will be looking at the factors influencing the CMM adoption and the benefits it perceive fiom it. Approximately 100 questionnaires were distributed to the staffs in those eight organisations names are not disclosed in this research due to confidentiality reason. A phone interview was also conducted to gain information personally fix>m the managers. Statistical analysis was carried out on data collected fix)m 50 completed questionnaires. As of the results, factors influencing the adoption process of CMM and the benefits it provided for all these eight organisations were identified.